INTEGRATION OF VOLLEYBALL EXERCISES FOR THE DEVELOPMENT OF COGNITIVE SKILLS IN SCHOOLCHILDREN (Scientific journal of the Fergana State University, 2025)
The article presents an analysis of the impact of the integration of volleyball exercises on the development of cognitive skills in schoolchildren of secondary school No. 25 in the city of Fergana. The main purpose of the study was to identify the effectiveness of game training in improving attention, memory and decision-making ability. The experiment was conducted for three months with the participation of 7th grade students, who were divided into control and experimental groups. The results confirming that the integration of volleyball exercises has a positive effect on the cognitive functions of students are presented.